2021
DOI: 10.1038/s41598-021-81214-7
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic on-chip production of microgels using combined geometries

Abstract: Microfluidic on-chip production of microgels using external gelation can serve numerous applications that involve encapsulation of sensitive cargos. Nevertheless, on-chip production of microgels in microfluidic devices can be challenging due to problems induced by the rapid increase in precursor solution viscosity like clogging. Here, a novel design incorporating a step, which includes a sudden increase in cross-sectional area, before a flow-focusing nozzle was proposed for microfluidic droplet generators. Bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…6a & b). The production of teardrop-shaped microgels indicated that complete gelation process or most of it occurred outside of the micro uidic device in the outlet tube [14], [34]. An observation that veri es this theory is the formation of spherical alginate droplets during our experiments.…”
Section: Of-chip Investigation Of Alginate Microgelssupporting
confidence: 76%
See 2 more Smart Citations
“…6a & b). The production of teardrop-shaped microgels indicated that complete gelation process or most of it occurred outside of the micro uidic device in the outlet tube [14], [34]. An observation that veri es this theory is the formation of spherical alginate droplets during our experiments.…”
Section: Of-chip Investigation Of Alginate Microgelssupporting
confidence: 76%
“…The micro uidic production of the microgels typically consists of two steps, including micro uidic emulsi cation of forerunner solutions and gelation of the produced droplets, which can be done in either on-chip or off-chip mode. The on-chip gelation method is commonly favored since it has numerous advantages over off-chip gelation, including simpli ed manipulation of the microgels' morphologies, facilitated way for loading a wide diversity of cargos, and continuous production of the microgels with an extraordinary degree of monodispersity [13], [14]. Yet, there are several outstanding challenges with the on-chip gelation method, one major factor being the immediate development of the cross-linking process, which may result in the occlusion of the microchannels and/or inlets and outlets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shieh et al . incorporated a shielding oil phase to avoid simultaneous emulsification and gelation of microspheres . Several groups have used the controlled release of calcium ions to trigger gelation on the chip for alginate systems. , Hou et al .…”
Section: Introductionmentioning
confidence: 99%
“…The microfluidic production of the microgels typically consists of two steps, including microfluidic emulsification of forerunner solutions and gelation of the produced droplets, which can be done in either on-chip or off-chip mode. The on-chip gelation method is commonly favored since it has numerous advantages over off-chip gelation, including simplified manipulation of the microgels’ morphologies, facilitated way for loading a wide diversity of cargos, and continuous production of the microgels with an extraordinary degree of monodispersity. , Yet, there are several outstanding challenges with the on-chip gelation method, one major factor being the immediate development of the cross-linking process, which may result in the occlusion of the microchannels and/or inlets and outlets. The production of microgel with controlled morphology and dispersity also requires the inclusion of a time lag between the emulsification and gelation processes .…”
Section: Introductionmentioning
confidence: 99%